2016
DOI: 10.21649/akemu.v12i2.904
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic trauma: effects of delay in presentation

Abstract: Objective: Hepatic trauma carries a substantial amount of morbidity & mortality. Purpose of study: The purpose of the study is to study the effects of delay in initiation of management of patients suffering from hepatic trauma. Design: Prospective study. Place & duration: The study was carried out in the Department of Surgery, Mayo Hospital Lahore from the year 1995-1997. Patient & methods: 57 patients were included in this study. They were operated and different methods of repair were employed. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Title and abstract screening excluded 1,889 records, and 66 full texts were evaluated. Twenty-four studies including 10,168 patients met the full eligibility criteria 9,16–38 . Reasons for exclusion included different patient population (n = 19), wrong exposure (n = 18), wrong study design (n = 4), and abstract without necessary data (n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Title and abstract screening excluded 1,889 records, and 66 full texts were evaluated. Twenty-four studies including 10,168 patients met the full eligibility criteria 9,16–38 . Reasons for exclusion included different patient population (n = 19), wrong exposure (n = 18), wrong study design (n = 4), and abstract without necessary data (n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Other proposed definitions of delay included 90 minutes from ED arrival to surgery for injuries to the aorta and inferior vena cava 16 and 3 to 4 hours from injury to hospital arrival for liver injuries requiring surgery. 35 Time cutoffs appeared to be selected after initial review of the data rather than a priori, where this information was provided. Remick and colleagues 18 analyzed time to mortality for patients who died from penetrating injuries within 4 hours, from which they concluded that delays of 43 minutes from injury to surgery would result in 50% mortality, while reducing this time to 19 minutes would potentially salvage 95% of patients.…”
Section: Definition Of Delaymentioning
confidence: 99%
See 3 more Smart Citations